Th17 and Th17/Treg ratio at early HIV infection associate with protective HIV-specific CD8(+) T-cell responses and disease progression - Falivene, Juliana (Sci Rep, 2015)
The aim of this study was to analyze Th17 and Treg subsets and their correlation with anti-HIV T-cell responses and clinical parameters during (acute/early) primary HIV infection (PHI) and up to one year post-infection (p.i). Samples from 14 healthy donors (HDs), 40 PHI patients, 17 Chronics, and 13 Elite controllers (ECs) were studied. The percentages of Th17 and Treg subsets were severely altered in Chronics, whereas all HIV-infected individuals (including ECs) showed Th17/Treg imbalance compared to HDs, in concordance with higher frequencies of activated CD8(+) T-cells (HLA-DR(+)/CD38(+)). Better clinical status (higher CD4 counts, lower viral loads and activation) was associated with higher Th17 and lower Treg levels. We found positive correlations between Th17 at baseline and anti-HIV CD8(+) T-cell functionality: viral inhibitory activity (VIA) and key polyfunctions (IFN-γ(+)/CD107(A/B)(+)) at both early and later times p.i, highlighting the prognostic value of Th17 cells to preserve an effective HIV T-cell immunity. Th17/Treg ratio and the IL-17 relative mean fluorescence intensity (rMFI of IL-17) were also positively correlated with VIA. Taken together, our results suggested a potential link between Th17 and Th17/Treg ratio with key HIV-specific CD8(+) T-cell responses against the infection.